ANALYSIS WORD CLASSES IN SELECTED POEMS BY ALLAN ALEXANDER MILNE - Nora Nopikasari; Ani Safitri; Agung Suhadi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
The objectives of this study are to investigate the word class or known as part of speech from the chosen poems of Alan Alexander Milne. For that reason, five poems of him are analyzed: Wrong House, Furry Bear, If I Were King, The Mirror, dan Hoppity. This study applies descriptive qualitative methods. The procedure of the study covers several steps; dividing words into word class category, analyzing them statistically and reporting the result. Out of the five analyzed poems, there are three-word class categories; verb, noun, an adjective. The most dominant used word class in the poems is noun comprising of 105 in total . This is due to the fact that noun is what the students most widely learned as beginner learners. In these poems, the noun describes the meaning of the poems. Therefore; the categorizing of the part of speech is important to enrich vocabulary and ease the understanding of the poem. This analysis is to make the readers easier in understanding the word class using a poem by Alan Alexander Milne